Protection of minority shareholders in the joint stock companies according to Saudi companies’ law - Afnan Mohammad Al-Farihi (International Journal of Law Research and Studies, 2026)
This study aimed to identify the means of protecting minority shareholders in joint-stock companies under the Saudi legal system by clarifying the concept of minority shareholders, identifying forms of majority abuse, and analyzing the legal, judicial, and regulatory mechanisms established to protect this category. The study problem centered on identifying the means of protecting minority shareholders from majority abuse under the Saudi legal system. The study adopted the descriptive-analytical approach through examining and analyzing the relevant legal provisions related to the subject matter and clarifying the scope of their application. The study reached several findings, most notably that the Saudi legislator has not provided an explicit definition of minority shareholders, rather, the concept is inferred from legal provisions. The study also found that the protection of minority shareholders in the Saudi legal system is based on an integrated framework combining legal, judicial, and regulatory mechanisms. Furthermore, investment awareness was identified as an important preventive dimension in protecting shareholders and enhancing their awareness of their rights and obligations. Based on the findings, the study presented several recommendations, the most significant of which are the necessity of establishing a legal definition for minority shareholders that precisely determines their legal scope, reconsider the first paragraph of Article (99) of the Companies Law to expand the scope of nullity claims to include cases of majority abuse, and establish clearer regulations regarding shareholders’ right to access information, including enabling shareholders to resort to the judiciary when they are unjustifiably denied this right without legal grounds.